2008
DOI: 10.1007/s10450-008-9137-6
|View full text |Cite
|
Sign up to set email alerts
|

Amine functionalised metal organic frameworks (MOFs) as adsorbents for carbon dioxide

Abstract: Three different porous metal organic framework (MOF) materials have been prepared with and without uncoordinated amine functionalities inside the pores. The materials have been characterized and tested as adsorbents for carbon dioxide. At 298 K the materials adsorb significant amount of carbon dioxide, the amine functionalised adsorbents having the highest CO 2 adsorption capacities, the best adsorbing around 14 wt% CO 2 at 1.0 atm CO 2 pressure. At 25 atm CO 2 pressure, up to 60 wt% CO 2 can be adsorbed. At h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
266
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(285 citation statements)
references
References 48 publications
14
266
2
3
Order By: Relevance
“…1,2 The first step in CO 2 reduction on heterogeneous catalyst surfaces is the activation of the C==O bond and charge transfer for the eventual formation of an anion radical species. 2 A significant number of studies exist in the literature regarding the adsorption, activation, and conversion of CO 2 using both heterogeneous, e.g., on metal/metal oxide surfaces [8][9][10][11] or metal-organic frameworks, [12][13][14][15] and homogeneous reactions, e.g., transition metal complexes. [16][17][18][19][20][21] More recently, transition metal sulfides have attracted significant attention for catalytic applications owing to their low cost, natural abundance, and prominent catalytic features.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The first step in CO 2 reduction on heterogeneous catalyst surfaces is the activation of the C==O bond and charge transfer for the eventual formation of an anion radical species. 2 A significant number of studies exist in the literature regarding the adsorption, activation, and conversion of CO 2 using both heterogeneous, e.g., on metal/metal oxide surfaces [8][9][10][11] or metal-organic frameworks, [12][13][14][15] and homogeneous reactions, e.g., transition metal complexes. [16][17][18][19][20][21] More recently, transition metal sulfides have attracted significant attention for catalytic applications owing to their low cost, natural abundance, and prominent catalytic features.…”
Section: Introductionmentioning
confidence: 99%
“…[3c,6-10] Nitrogen-containing groups or open metal sites accessible within the pores can improve CO 2 affinity via dipolequadrupole interactions with the CO 2 molecules. [11][12][13][14] We recently described the material NOTT-122 incorporating triazole groups which displays a high adsorption capacity for CO 2 and used a computational approach to investigate the specific interactions between CO 2 and the framework linker heteroatoms. [15] Similarly, Zaworotko et al have reported MOFs [16] containing amide functional groups in the linkers, whereby linking of three isophthalates generated polyhedral structures that exhibit a strong binding affinity to CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…S5 The excellent uptake of CO 2 observed in the low pressure isotherms is consistent with the presence of specific CO 2 -amide interactions. There are several potential interactions that can be proposed including dipole-quadrupole interactions of the type described above [11][12][13][14] and hydrogen-bond formation between the amide NH and the oxygens of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Other advantages of activated carbons over zeolites are the lower costs [8] and the higher resistance to water presence in the gas mixture [8,29,30]. Material science is very active in the research of new adsorbents with enhanced characteristics for CO2 separation [31][32][33][34]. Much effort is put in the laboratory tests to develop adsorbents with remarkable performance.…”
Section: Adsorbent Materialsmentioning
confidence: 99%